Internet Economy and Startup Business Development and Policy in Economic Law Perspectives - Krisharyanto, Edi; Purwadi, Ari (International Journal of Criminology and Sociology, 2021)
This study aims to analyze the development of startup business in Indonesia which is facing legal and regulatory barriers, namely legal issues, taxation, employment, intellectual property rights. By using a conceptual and empirical approach, the results showed that the fundamental legal problem faced by startup business in Indonesia is about the legality of establishing a startup business. Moreover, it relates to the legal standing of a business entity and its legal accountability. The theoretical implication of the findings underlines the startup business settings which are in need to be developed in the realm of economic law that leads to the regulation and legal thinking of ways to support the national economy. The practical implications suggest the development of startup business as a pioneering business entity in the field of commerce based on entrepreneurship and the internet economy.